Biostatistics of Hemorrhagic Fever Patients in Iraq (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
In this research, we will talk about Crimean-Congo hemorrhagic fever (CCHF), which is a severe tick-borne disease that spreads over a wide geographical area and has a case fatality rate of 30% or more. Cases due to CCHFV infection are reported throughout Africa, the Middle East, Asia, and southern and eastern Europe.Also, during this research, we will discuss some of the statistics and percentages that we collected through the field visit to some hospitals and health centers in Iraq, specifically in Dhi Qar Governorate, and we will also mention the results and suggestions that we reached through this visit.